Стратегия безопасности и возможность оптимизации параметров безопасности угольных шахт - Кобылянский, Борис Борисович; Мнухин, Анатолий Григорьевич (НТУ "ХПИ", 2015)
В статье рассмотрена стратегия обеспечения безопасности угольной промышленности, которая базируется исходно на системе представления научной информации для отрасли, включающей в себя учет последствий аварий с оценкой стоимостей человеческих жизней. В рамках проведенных исследований показано, что представление ячейки макросистемы, т.е. непосредственно шахты в виде эргатического объекта, дает возможность оптимизации параметров безопасности угольных шахт с учетом конкретных характеристик применяемого в ней оборудования, причем все упомянутые элементы расчетов или управления должны строиться исключительно на компьютерной основе.

The article describes the security strategy of the coal industry is based initially on the reporting system of scientific information to the industry, including the accounting of the consequences of accidents with the estimate of the cost of human lives, production management system industry, environmental factors and prognosis of complex multi-function universal phenomena. Selected issues of mentioned above strategy are the evaluation system of social phenomena, as well as the development of methods for recycling the coal industry and, in particular, the waste dumps. As part of the research shows that the representation of macro cells, that is, directly in the form of mines ergatic facility allows optimization of the parameters of safety of coal mines, taking into account the specific characteristics of the equipment used in it, all of these elements calculations or control shall be based solely on computer-based.
Security strategy and the ability to optimize the parameters of coal mine safety
Keywords: угольная промышленность; ячейка макросистемы; эргатический объект; управление угольной шахтой; macrosystem; ergatic object; efficiency; management of coal mine